Anti-ableism and scientific accuracy in autism research: a false dichotomy - Bottema-Beutel, Kristen; Kapp, Steven K.; Sasson, Noah; Gernsbacher, Morton Ann; Natri, Heini; Botha, Monique (Frontiers in Psychiatry, 2023)
It was recently argued that autism researchers committed to rejecting ableist frameworks in their research may sacrifice “scientifically accurate” conceptualizations of autism. In this perspective piece, we argue that: (a) anti-ableism vs. scientific accuracy is a false dichotomy, (b) there is no ideology-free science that has claim to scientific accuracy, and (c) autism science has a history of false leads in part because of unexamined ableist ideologies that undergird researcher framings and interpretations of evidence. To illustrate our claims, we discuss several avenues of autism research that were promoted as scientific advances, but were eventually debunked or shown to have much less explanatory value than initially proposed. These research programs have involved claims about autism etiology, the nature of autism and autistic characteristics, and autism intervention. Common to these false leads have been ableist assumptions about autism that inform researcher perspectives. Negative impacts of this work have been mitigated in some areas of autism research, but these perspectives continue to exert influence on the lives of autistic people, including the availability of services, discourses about autism, and sociocultural conceptualizations of autistic people. Examining these false leads may help current researchers better understand how ableism may negatively influence their areas of inquiry. We close with a positive argument that promoting anti-ableism can be done in tandem with increasing scientific accuracy.